Inflated Applicants: Attribution Errors in Performance Evaluation by Professionals - Swift, Samuel A.; Moore, Don A.; Sharek, Zachariah S.; Gino, Francesca (PLOS ONE, 2013)
When explaining others' behaviors, achievements, and failures, it is common for people to attribute too much influence to disposition and too little influence to structural and situational factors. We examine whether this tendency leads even experienced professionals to make systematic mistakes in their selection decisions, favoring alumni from academic institutions with high grade distributions and employees from forgiving business environments. We find that candidates benefiting from favorable situations are more likely to be admitted and promoted than their equivalently skilled peers. The results suggest that decision-makers take high nominal performance as evidence of high ability and do not discount it by the ease with which it was achieved. These results clarify our understanding of the correspondence bias using evidence from both archival studies and experiments with experienced professionals. We discuss implications for both admissions and personnel selection practices.